"I'm Not Gonna Die in This Damn Place" Manliness, Identity, and Survival of the Mexican American Vietnam Prisoners of War - David Coronado, Juan (Michigan State University Press, 2018)
By the time of the Vietnam War era, the "Mexican American Generation" had made tremendous progress both socially and politically. However, the number of Mexican Americans in comparison to the number of white prisoners of war (POWs) illustrated the significant discrimination and inequality the Chicano population faced in both military and civilian landscapes. Chicanos were disproportionately "grunts" (infantry), who were more likely to be killed when captured, while pilots and officers were more likely to be both white and held as POWs for negotiating purposes. A fascinating look at the Vietnam War era from a Chicano perspective, "I'm Not Gonna Die in this Damn Place": Manliness, Identity, and Survival of the Mexican American Vietnam Prisoners of War gives voice to the Mexican American POWs. The stories of these men and their families provide insights to the Chicano Vietnam War experience, while also adding tremendously to the American POW story. This book is an important read for academics and military enthusiasts alike.